CREATOR CONTENT COMMUNICATION STRATEGY IN MAINTAINING THE EXISTENCE OF THE LAPOR PAK COMEDY EVENT PROGRAM - Nurmanita, Kurnia Intisyah; Umarella, Farid Hamid (Universitas Mercu Buana, 2025)
In the era of convergence, conventional media must follow the current developments of the times. industry players, especially in the creative television industry, must not turn a blind eye to the current conditions so as not to be degraded and eroded by the rapid flow of technological development. One of the program programs, namely Lapor Pak, sees this condition and tries to take advantage of it in an effort to maintain its existence amidst the Covid-19 pandemic and the emergence of other comedy sketch programs. This research uses a case study method with a constructivist paradigm with data collection techniques in the form of interviews, observation, document study and literature study. The research results show that the Lapor Pak Program can maintain its existence by utilizing the convergence of media such as YouTube, Tiktok and Instagram, apart from that the Lapor Pak Program has succeeded in creating its own characteristics for its program, making it different from other comedy sketch shows. The supporting factors for the Lapor Pak program in maintaining its existence are strong chemistry between the players, each player in Lapor Pak has its own comedic character so that the comedy message can be conveyed well, and a variety of guest stars, while the inhibiting factor for the Lapor Pak Program is the implementation of policies. PPKM by the government resulted in the report sir program not being broadcast for several days.